History of vigorous leisure-time physical activity and early onset amyotrophic lateral sclerosis (ALS), data from the national ALS registry: 2010–2018. Issue 7 (2nd October 2021) - Raymond, Jaime; Mehta, Paul; Larson, Ted; Factor-Litvak, Pam; Davis, Bryn; Horton, Kevin
Abstract: Background : Previous research has suggested that vigorous physical activity (VPA) during adolescence and early adulthood is associated with ALS. The National ALS Registry (Registry) collects physical activity data from persons with ALS. Objective: To examine the association between vigorous VPA and early onset ALS, defined as a diagnosis before age 60, among patients enrolled in the Registry. VPA was defined as engaging in dynamic exercise for at least 10 minutes in a session that caused heavy sweating or large increases in breathing or heart rate. Methods: A cross-sectional study was conducted of 5463 ALS patients with VPA history and 956 ALS patients who never engaged in VPA. Patient characteristics were collected via online surveys in the following areas: demographic, lifetime VPA history, and initial onset of symptoms. General linear modeling was used to estimate mean age of diagnosis and to compute 95% confidence intervals. Results: Patients who reported engaging in VPA at least moderately (three times a week) during early adulthood were more likely to have an ALS diagnosis earlier compared to patients who did not ( p < 0.0001). After controlling for year of birth, statistically significant associations between those reporting VPA at age 15–24 and 25–34 and diagnosis of ALS earlier ( p = 0.0009, p = 0.0144 respectively). Conclusion: Patients with ALS who had a history of VPA before age 35, were significantly more likely to be diagnosed with ALS before age 60 compared to patients with ALS who never engaged vigorously. More research is needed in the relationship between VPA and early onset ALS.